MONITORING DEGRADATION OF WETLAND AREAS USING SATELLITE IMAGERY AND GEOGRAPHIC INFORMATION SYSTEM TECHNIQUES - & Jaber, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
In order to conserve the ecosystems and biodiversity of wetland areas, it is necessary to monitor the degradation of these areas. Currently, Al Razzazah lake and its surrounding areas have degradation significantly due to its low water level, which has negatively affected its biodiversity. Hence, this   research aims to propose a method to model the monitoring of spatio-temporal changes in that lake and its surrounding areas with an area estimated at 4660 km² between (1998 – 2018) using Remote Sensing and Geographic Information System (GIS) techniques. After conducting the supervised classification by the method of Support Vector Machine (SVM) for all satellite images, we extracted thematic maps, which contain five classes. The results showed the overall accuracy was 90.11%, 91.60% and 90.57% while the Kappa coefficient were 0.8764, 0.8950 and 0.8821 for 1998, 2008 and 2018 respectively. Results showed that the lake area decreased by 86.21% in the study area in 2018.